ANALYSIS OF FACTORS CONTRIBUTING TO WORK STRESS AMONG EXPATRIATE AIRLINES CREW IN SAUDI ARABIA - Molina, Prima; Teresa; V.V Satvika, Maharani; E. Gunawan, Fergyanto (JARES (Journal of Academic Research and Sciences), 2024)
Work stress can significantly impact the performance of cabin crew in the airline industry, potentially leading to job errors with critical implications for safety, a paramount concern in the industry. The research focuses on factors influencing work stress among cabin crew, providing a valuable reference for improving both service quality and safety in the industry. The potential key factors that affect work stress, including workload, cross-cultural adjustment, rotating work schedules, interpersonal relationships, organizational relationships, and physical demands, are established through extensive literature reviews. The relevant data were collected from a sample of cabin crews in Saudi Arabia representing various nationalities. The most pertinent factors for the problem setting are determined by applying a multivariate regression analysis, where the theoretical understanding is statistically verified. The analysis suggests that the theory is supported by the sample data with a fitness level of 0.85 in terms of the determination coefficient, implying strong materialization of the theory. Furthermore, the agreement between theory and reality is supported by the ANOVA and t-tests. The study concludes that workload is the most dominant factor affecting work stress, followed by organizational relationships and rotating work schedules. Statistically less significant factors include cross-cultural adjustment, interpersonal relationships, and physical demands.